Synthesis and properties of iron silicides - Pavel Novák; Ester Duchková; Andrea Boháčová; Alena Michalcová; Filip Průša; Kateřina Skotnicová; Ivo Szurman (Journal of Materials Research and Technology)
Composite materials based on aluminide matrix and hard silicide reinforcement are currently considered as potential tool materials. However, the reasonable design of the composites is limited by incomplete available information about the properties of suitable silicides. Therefore, this work focuses on the synthesis and characterization of iron silicides, which could be very promising also due to the low price of the constituents. The synthesis route for individual iron silicides (Fe3Si, FeSi, FeSi2) was investigated using a combination of mechanical alloying, spark plasma sintering, and homogenization annealing. In the case of Fe5Si3, which is thermodynamically stable at the temperatures above 825 °C, homogenization annealing was followed by water quenching. The synthesized iron silicides were characterized from the viewpoint of phase composition, microstructure, hardness and abrasive wear resistance. As the hardest silicide, Fe5Si3 was proved; however, it was only obtained in coexistence with other phases due to its low thermodynamic stability. Among the stable iron silicides, FeSi phase offers the best combination of hardness and tribological properties.